Prevalência da queilite actínica em uma população brasileira - Miranda, Ana Maria de Oliveira (2009)
AC is defined as a degenerative condition of the epithelium covering caused by ultraviolet radiation of the sun on the lips. It is considered a cancerous lesion that can evolve into lip carcinoma. A study was conducted on the prevalence of AC in 1,539 individuals from the agricultural population who worked for a sugar cane plant under conditions which exposed them to the sun. A group of 150 individuals with no exposure to the sun were put in a “control group” in which no cases of AC were found. Of the 141 (9.6%) cases of AC that had been found, 106 were men, 36 women and 128 were in leucodermas. Regarding the severity of lesions 39 had been classified as light, 57 as moderate and 45 as severe. The longer the exposure to the sun the more cases of AC had been observed.